(9x-7)(x+4)=

Simple and best practice solution for (9x-7)(x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9x-7)(x+4)= equation:


Simplifying
(9x + -7)(x + 4) = 0

Reorder the terms:
(-7 + 9x)(x + 4) = 0

Reorder the terms:
(-7 + 9x)(4 + x) = 0

Multiply (-7 + 9x) * (4 + x)
(-7(4 + x) + 9x * (4 + x)) = 0
((4 * -7 + x * -7) + 9x * (4 + x)) = 0
((-28 + -7x) + 9x * (4 + x)) = 0
(-28 + -7x + (4 * 9x + x * 9x)) = 0
(-28 + -7x + (36x + 9x2)) = 0

Combine like terms: -7x + 36x = 29x
(-28 + 29x + 9x2) = 0

Solving
-28 + 29x + 9x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-4 + -1x)(7 + -9x) = 0

Subproblem 1

Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4

Subproblem 2

Set the factor '(7 + -9x)' equal to zero and attempt to solve: Simplifying 7 + -9x = 0 Solving 7 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -9x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -9x = 0 + -7 -9x = 0 + -7 Combine like terms: 0 + -7 = -7 -9x = -7 Divide each side by '-9'. x = 0.7777777778 Simplifying x = 0.7777777778

Solution

x = {-4, 0.7777777778}

See similar equations:

| z^3+iz^2-iz+1=0 | | xa-19=0 | | -40=7y-3x | | 1/4y=x | | 3/4=n/75 | | Cos(2x)+cos(x)=9 | | 0.04p+48=p | | 5(x+7)+10=7x-2(x-5) | | a^2+7a+10=10 | | -2x=6y+16 | | x^2+(m+1)x+m+2=0 | | 28xy^2+5xy-3-(25xy^2+6-xy)=0 | | 3(x-6)+2=3x-11 | | -[5-(a+1)]=9-[(2a-3)] | | 3(5c-1)2=13c+3 | | 3(x-6)=x-19 | | 14n-8=24 | | c=4x+5 | | X^4+10X^2+18=0 | | 3x-18=6x+21 | | 58.5=35x-6 | | a(12-n)= | | 9z+4-7z=49-7z | | 2(-3p-6)=3[-4p-3(p+2)] | | 28+36+6(-7x+x)=2(5x-6) | | -4p-5=15 | | -16tx^2+21x-6=0 | | 6(a-8)+16=4(a-7) | | 6x-4(6-x)=2 | | Cot3x/5=-1 | | 28+36+6(-7x+c)=2(5x-6) | | 32+2x=12-7x |

Equations solver categories